Arabidopsis DXO1 links RNA turnover and chloroplast function independently of its enzymatic activity. Issue 9 (14th February 2019) - Kwasnik, Aleksandra; Wang, Vivien Ya-Fan; Krzyszton, Michal; Gozdek, Agnieszka; Zakrzewska-Placzek, Monika; Stepniak, Karolina; Poznanski, Jaroslaw; Tong, Liang; Kufel, Joanna
Abstract: The DXO family of proteins participates in eukaryotic mRNA 5′-end quality control, removal of non-canonical NAD + cap and maturation of fungal rRNA precursors. In this work, we characterize the Arabidopsis thaliana DXO homolog, DXO1. We demonstrate that the plant-specific modification within the active site negatively affects 5′-end capping surveillance properties of DXO1, but has only a minor impact on its strong deNADding activity. Unexpectedly, catalytic activity does not contribute to striking morphological and molecular aberrations observed upon DXO1 knockout in plants, which include growth and pigmentation deficiency, global transcriptomic changes and accumulation of RNA quality control siRNAs. Conversely, these phenotypes depend on the plant-specific N-terminal extension of DXO1. Pale-green coloration of DXO1-deficient plants and our RNA-seq data reveal that DXO1 affects chloroplast-localized processes. We propose that DXO1 mediates the connection between RNA turnover and retrograde chloroplast-to-nucleus signaling independently of its deNADding properties.